The Role of the University Teacher in Oral Health: Towards Comprehensive and Transformative Training (Docentes 2.0 Journal, 2025)
In the university context, the role of oral health instructors is indispensable, not only because they are responsible for transmitting technical knowledge but also because of their responsibility to train professionals committed to a comprehensive, ethical, and transformative vision of health. This postdoctoral research aimed to investigate the role of university instructors in oral health to promote comprehensive and transformative training that responds to the sector's current needs. The research was conducted within the humanistic paradigm, with a hermeneutic method, a qualitative approach, a narrative design, an interpretive approach, and a cross-sectional approach. The study was conducted with a purposive sample of 10 university instructors from the Faculty of Dentistry at the Central University of Venezuela, selected for their academic background, clinical experience, and willingness to participate. Semi-structured interviews and open-ended questionnaires validated by expert judgment were used to collect data. Data analysis was performed using thematic coding with the support of Atlas. ti software, allowing for identifying emerging categories such as perception of the teaching role, integration of bioethics, and pedagogical training needs. The results reveal a gap between current teaching practice and the principles of transformative education. It is concluded that it is urgent to implement institutional strategies that strengthen university professors' pedagogical, ethical, and reflective training geared toward social well-being and improving public health.
Keywords: Role of university professors; oral health; comprehensive transformative training